The qacC Gene Has Recently Spread between Rolling Circle Plasmids of Staphylococcus, Indicative of a Novel Gene Transfer Mechanism - Wassenaar, Trudy M. (Front Microbiol, 2016)
Resistance of Staphylococcus species to quaternary ammonium compounds, frequently used as disinfectants and biocides, can be attributed to qac genes. Most qac gene products belong to the Small Multidrug Resistant (SMR) protein family, and are often encoded by rolling-circle (RC) replicating plasmids. Four classes of SMR-type qac gene families have been described in Staphylococcus species: qacC, qacG, qacJ, and qacH. Within their class, these genes are highly conserved, but qacC genes are extremely conserved, although they are found in variable plasmid backgrounds. The lower degree of sequence identity of these plasmids compared to the strict nucleotide conservation of their qacC means that this gene has recently spread. In the absence of insertion sequences or other genetic elements explaining the mobility, we sought for an explanation of mobilization by sequence comparison. Publically available sequences of qac genes, their flanking genes and the replication gene that is invariably present in RC-plasmids were compared to reconstruct the evolutionary history of these plasmids and to explain the recent spread of qacC. Here we propose a new model that explains how qacC is mobilized and transferred to acceptor RC-plasmids without assistance of other genes, by means of its location in between the Double Strand replication Origin (DSO) and the Single-Strand replication Origin (SSO). The proposed mobilization model of this DSO-qacC-SSO element represents a novel mechanism of gene mobilization in RC-plasmids, which has also been employed by other genes, such as lnuA (conferring lincomycin resistance). The proposed gene mobility has aided to the wide spread of clinically relevant resistance genes in Staphylococcus populations.